The Effect of Transformational Leadership and Compensation on Employee Performance and Loyalty and Its Impact on Organizational Citizen Behavior at PT. Yarindo Farmatama - Vembri Widyadi Utomo (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study analyses the effect of transformational leadership, compensation on employee performance and loyalty on Organizational Citizen Behavior at PT. Yarindo Farmatama, either partially or simultaneously. The methodology used for this study is a quantitative approach with an explanatory design. In this study, the data collection technique is done with the distribution of questionnaires to the PT. Yarindo Farmatama employees. The data type that is used for this study is primary data. The population of this study is all of PT. Yarindo Farmatama's employees, which consists of 273 employees. The sample's withdrawal is made by using probability sampling, with the technique of simple random sampling. There are 56 respondents for the models in this study. The data analysis method used in this study is multiple regression. The result of the study has shown that transformational leadership (X1) and compensation for employee performance (X2) do not have a significant influence on Organizational Citizen Behavior (Y). The value of sig X1 (0.545) and X2 (0.196) is more potent than 0.05. The loyalty of the employees (X3) showed significant influence towards Organizational Citizen Behavior, with the value of sig 0,000, which is smaller than 0,005. However, the variables X1, X2, and X3 have a significant and positive influence on variable Y. The results of the coefficient of determination test obtained an adjusted r-square value of 65.7%. It means that the contribution of the variables X1, X2, and X3 combined has dramatically influenced the Y variable as much as 65.7%. In comparison, the remaining 32.3% is influenced by other factors outside the variables of this study. Keyword : Transformational Leadership, Compensation, Loyalty, Organizational Citizen Behavior (OCB)..